Pengaruh Kompensasi dan Fasilitas Kerja terhadap Kinerja Karyawan Melalui Kepuasan Kerja di PT Bali Coklat Junglegold Bali - Aliya Rizky Ayuningtyas; Ni Luh Prima Kemala Dewi (BADAN PENERBIT STIEPARI PRESS, 2025)
Human Resources (HR) is an important factor in improving company performance, where employee performance is a key factor in company achievement. This study aims to analyze the effect of compensation and work facilities on employee performance, both directly and indirectly, through job satisfaction as an intervening variable. Job satisfaction is seen as an important element that bridges the relationship between compensation and work facilities with increased individual performance. The study was conducted at PT Bali Coklat Junglegold Bali with a sample of 76 respondents through the census sampling method. Data analysis used the Structural Equation Modeling (SEM) method with the Smart PLS Program. The results of this study indicate that, 1) Compensation and work facilities partially have a significant effect on employee performance. 2) Compensation and work facilities partially have a significant effect on employee job satisfaction. 3) Job satisfaction partially has a significant effect on employee performance. 4) Compensation and work facilities partially have a significant effect on employee performance through job satisfaction as a mediating variable at PT Bali Coklat Junglegold Bali. Companies are advised to pay more attention to increasing job satisfaction through providing fair compensation and providing adequate work facilities so that employees can work more optimally and productively.